PERSEPSI MAHASISWA DEPARTEMEN ILMU INFORMASI DAN PERPUSTAKAAN FBS UNP ANGKATAN 2021TERHADAP PENCARIAN INFORMASI MENGGUNAKAN CHATGPT - Hakim, Muhammad; Desriyeni, Desriyeni (Scinary, 2023)
This study examines the perceptions of students of the Department of Information Science and Library FBS UNP Class of 2021 towards information search using ChatGPT. This research uses quantitative descriptive methods. The research population was 249 students with a sample of 72 students. The sampling technique used simple random sampling technique. Data analysis in this study by verifying the data, then tabulating and processing the data by calculating using the mean formula to calculate the average per statement item, as well as calculating the grand mean to calculate the total average of each indicator. The results showed that the perceptions of students of the Department of Information Science and Library FBS UNP 2021 Angaktan towards information search using ChatGPT have responded well.